Food addiction, executive function and mood in adolescents with obesity seeking treatment. (1st April 2021) - Vidmar, Alaina P.; Wee, Choo Phei; Salvy, Sarah J.
Abstract: Background: The relationships between food addiction, executive functions and mood in adolescence are not well-understood. This study examines differences in executive functioning, depression symptoms and perceived stress among adolescents with obesity with- and without food addiction. Methods: A total of 110 adolescents with obesity (74 females; age = 15.59 ± 1.3 y; 67% Hispanic; 74% public insurance) completed the Behavior Rating Inventory of Executive Function-2 (BRIEF-2), the Yale Food Addiction Scale for children (YFAS-c), the Perceived Stress Scale (PSS) and the Center for Epidemiologic Studies Depression scale (CES-DC). Chi-squared and Fisher's exact tests were used to evaluate differences in BRIEF-2, CES-DC and PSS scores between participants with and without food addiction. A logistic regression model assessed the associations between executive dysfunction, depression and stress on food addiction individually. Multiple logistic regression was utilized to further examine the association between executive dysfunction and food addiction when accounting for depression and stress. Results: More than a third of participants (34.5%) met the criteria for food addiction. Females were 2.89 times more likely than males to have food addiction (95th%CI = 1.12–7.46, p = 0.03). Participants with FA had significantly higher BRIEF-2 T-scores (all p < 0.05) and higher PSS and CES-DC scores (all p < 0.05). Multiple logistic regression analysis showed depression was strongly correlated with FA when controlling for executive dysfunction and stress ( p = 0.010). Conclusions: Among obesity treatment-seeking adolescents, youths with food addiction displayed greater impairments in executive functioning and higher levels of stress and depressive symptoms than adolescents without food addiction. Prospective studies are needed to determine how this behavioral phenotype helps predict intervention outcomes.